Environmental adaptation, growth performance and nutrient content of the clam Cyclina sinensis from different geographic locations - Yan, Shiyu; Xia, Qing; Cui, Zhenquan; Ren, Guoliang; Li, Xiaoying; Ge, Hongxing; Liu, Meimei; Dong, Zhiguo (Frontiers in Marine Science, 2024)
The clam Cyclina sinensis is an economically important marine species in China. However, overfishing, habitat destruction, and inbreeding have led to the destruction of genetic resources. In this study, five natural populations [Dandong (DD), Dongying (DY), Tianjin (TJ), Wenzhou (WZ), and Yancheng (YC)] from different geographical locations were relocated and cultured homogeneously to study their potential for translocation and environmental adaptation by observing growth performance and nutrient content. There were significant differences in the growth rates of shell length (SL), shell height (SH), and shell width (SW) among the five populations (P<0.05). The DD, TJ, and YC populations exhibited the highest SL and SH growth rates, whereas these were lowest in the WZ population. The survival rate was highest in the YC population and lowest in the WZ population, which was significantly lower than the other four populations (P<0.05). The DD population exhibited superior plumpness and glycogen content, and the overall glycogen content in male C. sinensis was higher compared with that in females (P<0.05). All populations displayed a high total amino acid content and the essential amino acid/Total Amino Acid (EAA/TAA) and Non-essential amino acid/Total Amino Acid (NEAA/TAA) ratios in the soft tissue of all five populations aligned with the FAO/WHO ideal protein evaluation standards. Despite the same aquaculture environment, however, the nutrient composition of C. sinensis sampled from different populations varied significantly (P<0.05).Therefore, ex situ conservation did not eliminate nutritional differences between the different populations of C. sinensis. These findings highlight the importance of considering environmental and ecological factors in the nutritional assessment and cultivation of shellfish. In addition, C. sinensis from sampling sites closer to the transplantation sites had higher survival rates and growth rates, and the gonadal development of all populations showed adaption to the local environment, resulting in synchronization of the reproductive period.